Catheter ablation of atrial fibrillation in patients with autoimmune disease: A propensity score matching study based on the China Atrial Fibrillation Registry - Gao, Ming‐Yang; Huang, Li‐Hong; Lai, Yi‐Wei; Guo, Qi; Guo, Xue‐Yuan; Li, Song‐Nan; Jiang, Chen‐Xi; Liu, Nian; He, Liu; Li, Xu; Tang, Ri‐Bo; Du, Xin; et al. (Clinical cardiology (Mahwah, N.J.), 2023)
Background Evidence on outcomes of catheter ablation (CA) for atrial fibrillation (AF) in patients with autoimmune disease (AD) is limited. Hypothesis Patients with AD had worse outcomes after CA procedures for AF. Methods A retrospective analysis was performed in patients undergoing AF ablation between 2012 and 2021. The risk of recurrence after ablation was investigated in patients with AD and a 1:4 propensity score matched non‐AD group. Results We identified 107 patients with AD (64 ± 10 years, female 48.6%) who were matched with 428 non‐AD patients (65 ± 10 years, female 43.9%). Patients with AD exhibited more severe AF‐related symptoms. During the index procedure, a higher proportion of AD patients received nonpulmonary vein trigger ablation (18.7% vs. 8.4%, p = 0.002). Over a median follow‐up of 36.3 months, patients with AD experienced a similar risk of recurrence with the non‐AD group (41.1% vs. 36.2%, p = 0.21, hazard ratio [HR]: 1.23, 95% confidence interval [CI]: 0.86–1.76) despite a higher incidence of early recurrences (36.4% vs. 13.5%, p = 0.001). Compared with non‐AD patients, patients with connective tissue disease were at an increased risk of recurrence (46.3% vs. 36.2%, p = 0.049, HR: 1.43, 95% CI: 1.00–2.05). Multivariate Cox regression analysis showed that the duration of AF history and corticosteroid therapy were independent predictors of postablation recurrence in patients with AD. Conclusions In patients with AD, the risk of recurrence after ablation for AF during the follow‐up was comparable with non‐AD patients, but a higher risk of early recurrence was observed. Further research into the impact of AD on AF treatment is warranted. In this study conducted at Beijing Anzhen Hospital, we investigated the association between autoimmune diseases (AD) and procedural characteristics and recurrence after catheter ablation for atrial fibrillation in 107 patients with AD (AD group) and 428 propensity score‐matched patients without AD (non‐AD group). During the index procedure, a higher proportion of AD patients received nonpulmonary vein trigger ablation. Over a median follow‐up of 36.3 months, patients with AD experienced a similar risk of recurrence with the non‐AD group despite a higher incidence of early recurrences.